EKSPERIMENTASI MODEL PEMBELAJARAN PENEMUAN TERBIMBING, PAIR CHECKS, DAN THINK PAIR SHARE PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI GAYA BELAJAR - Muawanah, Lina; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of this study was to determine the effect of guided discovery learning model, Pair Check (PC), and Think Pair Share (TPS) on the mathematics achievement of students in terms of student learning styles. This research used the quasi-experimental with factorial design 3x3. The population of this research was all Junior High School eighth grade students in Semarang Regency that used KTSP 2006. The sampling technique was conducted by stratified cluster random sampling. The instruments used to collect data were mathematics achievement test and questionnaire learning styles. The data was analyzed using two ways ANOVA with unbalanced cell, then then preceded with multiple comparative test using Scheffe method. Based on the hypothesis test, the results of this research obtained the following conclusions. 1) Guided discovery learning model provided a better learning achievement than learning model PC and TPS, as well as learning model TPS and PCÂ  provided the same learning achievement. 2) Students with a visual learning style had better learning achievement than the students with auditory and kinesthetic learning styles, as well as students with auditory and kinesthetic learning styles had the same learning achievement. 3) In each learning model that guided discovery, PC and TPS, students with learning styles visual, auditory and kinesthetic provided the same mathematics learning achievement (4) In each of the students with visual and kinesthetic learning styles, learning model guided discovery, PC, and TPS had the same learning achievement. At the students with auditory learning styles, learning models had guided discovery learning achievement were better than a PC, the PC and TPS learning model had the same mathematics achievement, as well as guided discovery learning model and TPS had the same mathematics achievement.Keywords: Learning model, cooperative learning, guided discovery, PC, TPS, learning styles, learning achievement in Mathematics